2010
DOI: 10.1063/1.3474618
|View full text |Cite
|
Sign up to set email alerts
|

Carrier hopping in disordered semiconducting polymers: How accurate is the Miller–Abrahams model?

Abstract: We performed direct calculations of carrier hopping rates in strongly disordered conjugated polymers based on the atomic structure of the system, the corresponding electronic states and their coupling to all phonon modes. We found that the dependence of hopping rates on distance and the dependence of the mobility on temperature are significantly different than the ones stemming from the simple Miller-Abrahams model, regardless of the choice of the parameters in the model. A model that satisfactorily describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 18 publications
3
59
0
Order By: Relevance
“…It was shown for example that the distance dependence normally included in the Miller-Abrahams rate is too approximate. 25 This was later found also in ref. 23 where the importance of variable localization of states was highlighted.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…It was shown for example that the distance dependence normally included in the Miller-Abrahams rate is too approximate. 25 This was later found also in ref. 23 where the importance of variable localization of states was highlighted.…”
Section: Introductionsupporting
confidence: 65%
“…A similar conclusion was achieved with different arguments in ref. 25 . Moreover, if quantum inducing modes are not too important, one can neglect them altogether using the equation valid in the classical limit of inducing modes (eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following ref. [14] we incorporate the effect of the distance between initial and final states by parametrizing the coupling as …”
Section: B Exp a E K T  mentioning
confidence: 99%
“…Notably, recent work has suggested that deviations from these hopping rates can be observed from first-principles simulations. 26 To capture the dynamic disorder, model Hamiltonians such as Holstein and Peierls types have been widely used but with mixed success, 27−29 partly because these model Hamiltonians are based on perturbation theories and thus are restricted to specific ranges of microscopic parameters. More importantly, the aforementioned models are not materialspecific and contain empirical parameters that need to be predetermined; thus they lack predictability that is crucial for computational materials design.…”
Section: ■ Introductionmentioning
confidence: 99%